2018
DOI: 10.1159/000493142
|View full text |Cite
|
Sign up to set email alerts
|

Differential Peripheral Inflammatory Factors Associated with Cognitive Function in Patients with Heart Failure

Abstract: Objective: Cognitive deficits are common in patients with heart failure (HF), and can negatively affect self-care, predict rehospitalizations, and increase mortality rates 5-fold. Inflammation can produce vascular pathology, reducing cerebral blood flow to brain regions necessary for optimal cognitive function. The purpose of the investigation was to identify a pattern of peripheral blood inflammation-related biomarkers associated with cognitive impairment in patients with HF. Methods: Forty-five outpatients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“… 55 In patients with Alzheimer disease, there is a meaningful correlation between inflammatory mediators and GCF. 56 57 Moreover, it has been shown that the plasma of patients with COPD often contains abnormal levels of inflammatory mediators, including IL-6, IL-8, CRP, TNF-α and BDNF. 58–60 Therefore, in this study, we seek to observe whether PR can affect GMV and blood inflammatory mediators and to explore the possible mechanism by which exercise affects cognitive function in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“… 55 In patients with Alzheimer disease, there is a meaningful correlation between inflammatory mediators and GCF. 56 57 Moreover, it has been shown that the plasma of patients with COPD often contains abnormal levels of inflammatory mediators, including IL-6, IL-8, CRP, TNF-α and BDNF. 58–60 Therefore, in this study, we seek to observe whether PR can affect GMV and blood inflammatory mediators and to explore the possible mechanism by which exercise affects cognitive function in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our previous cross-sectional study revealed that patients with HF and MCI had greater circulating peripheral vascular inflammation marker levels compared to patients without MCI (27). Another study found a negative relationship between peripheral inflammation biomarkers, C-reactive protein (CRP) and interleukin-6 (IL-6), and cognitive function in patients with HF (28).…”
mentioning
confidence: 99%
“…Cardiovascular disease (CVD) is a common chronic condition that disproportionately affects older adults [1]. Prior studies have shown a connection between CVD and cognitive impairment [2][3][4][5][6][7][8], with multiple potential mechanisms at play, including atherosclerotic-related cerebrovascular disease (causing cerebral hypoxia, brain infarctions, and damage to the blood-brain barrier) [9][10][11]; oxidative stress and inflammatory immune responses [12,13]; and thromboembolism from concomitant atrial fibrillation [14,15]. More recently, several longitudinal studies have indicated that incident CVD is associated with an acceleration in the decline in memory and processing speed that occurs normally with age [16][17][18].…”
Section: Introductionmentioning
confidence: 99%